2018
DOI: 10.1108/ebhrm-04-2018-0030
|View full text |Cite
|
Sign up to set email alerts
|

Organizational justice and turnover intentions: probing the Pakistani print media sector

Abstract: Purpose To survive in this competitive era of modern business environment, organizations have to constantly develop, adapt and react to new challenges. Therefore, it is critical for organizations to create a sense of justice and involve their employees in business activities; thereby achieving the organization’s strategic goals. The purpose of this paper is to investigate the impact of organizational justice (OJ) on job turnover behavior of employees within the print media sector of Pakistan. Design/methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 69 publications
3
31
0
Order By: Relevance
“…Blakely, Andrews and Moorman (2005), Tyagi, Moses and Rana (2017) reached to the results in their studies that the participants' organizational justice perceptions were high. Hussain and Khan (2018) found in their study that the staff's procedural justice perceptions were moderate, distribution as justice perceptions were low and interactional justice perceptions were high.…”
Section: Discussionmentioning
confidence: 93%
“…Blakely, Andrews and Moorman (2005), Tyagi, Moses and Rana (2017) reached to the results in their studies that the participants' organizational justice perceptions were high. Hussain and Khan (2018) found in their study that the staff's procedural justice perceptions were moderate, distribution as justice perceptions were low and interactional justice perceptions were high.…”
Section: Discussionmentioning
confidence: 93%
“…It is similar to instructions and demonstrations on handling a particular task (Grondelle, 2018;Pepper, 2019). A study done by Mueller and Price found that an intention to leave is formed when there is a sense of the unfair distribution of rewards and outcomes among employees (Hughes & Merges, 2017;Hancock et al, 2018;Hussain & Khan, 2019;Brinkmann, 2020). H1: Organisational justice is related to employees' voluntary turnover.…”
Section: Organisational Justice and Turnovermentioning
confidence: 99%
“…Perceived distributive justice has been shown to affect employees' work attitudes and behaviors, including job satisfaction, retention, and withdrawal (Daileyl & Kirk, 1992;Sweeney & McFarlin, 1997). In particular many scholars, including Telly et al (1971) and Hussain and Khan (2019), have found that employee turnover intention is significantly related to distributive justice. Consistent with this previous research, we hypothesize the following: Hypothesis 2b: Regarding HL identification, the perceived distributive justice of coworkers who have not been identified as HLs in project teams is negatively related to their turnover intentions.…”
Section: The Mediating Role Of Perceived Distributive Justicementioning
confidence: 99%